2013
DOI: 10.1155/2013/495703
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic Effects of EGb 761

Abstract: Ginkgo biloba extracts have long been used in Chinese traditional medicine for hundreds of years. The most significant extract obtained from Ginkgo biloba leaves has been EGb 761, a widely used phytopharmaceutical product in Europe. EGb 761 is a well-defined mixture of active compounds, which contains two main active substances: flavonoid glycosides (24–26%) and terpene lactones (6–8%). These compounds have shown antiapoptotic effects through the protection of mitochondrial membrane integrity, inhibition of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 181 publications
(186 reference statements)
1
11
0
1
Order By: Relevance
“…These findings agree with Serrano-García et al [55], who reported that Ginkgo biloba administration reduced the ischemia and I/R induced damage in testicular tissue. Ginkgo biloba has antiapoptotic effects through the protection of mitochondrial membrane integrity, possibly by its flavonoid constituents [56], which was manifested in the present study, by decreased mitochondrial NAD + in Ginkgo biloba treated I/R group.…”
Section: Discussionsupporting
confidence: 92%
“…These findings agree with Serrano-García et al [55], who reported that Ginkgo biloba administration reduced the ischemia and I/R induced damage in testicular tissue. Ginkgo biloba has antiapoptotic effects through the protection of mitochondrial membrane integrity, possibly by its flavonoid constituents [56], which was manifested in the present study, by decreased mitochondrial NAD + in Ginkgo biloba treated I/R group.…”
Section: Discussionsupporting
confidence: 92%
“…expression of GCLC, BDNF, BCL-2, and GSH; inhibits serotonin degradation by MAO, liberation of the Cytochrome C, activity of Caspase-3, fragmentation of the internucleosome DNA, NADH, activation of p53 protein, p65 protein, NF-κB and apoptosis; decrease in the neurotoxicity induced through 3-NP and the elevation of BAX through ROS; elimination of free radicals; and upregulation of HMOX-1 [43,74,75]. QuercetinIncrease the level of BDNF; inhibition of degradation of serotonin by MAO, apoptosis; transcription of TNF-α; activation of ERK, phosphorylation, and activation of JNK; decrease of lipid peroxidation in the plasma and phosphorylation of IkBβ; upregulation of HMOX-1; and elimination of free radicals.…”
mentioning
confidence: 99%
“…In addition, some research ers have found that the activation of TNFa, IL6, and IL-18, and the activation of the nuclear factor (NF) kB pathway can lead to inflammation cascade effects and tissue damage (Morris et al, 1989;Neurath et al, 1997). The downregulation of these cytokines seems to be important for the prevention of cell apoptosis (SerranoGarcía et al, 2013). The reason for the de creases seen in the levels of these cytokines following treatment with G. biloba may be due to a homeostatic mechanism involving the flavonoids and polysaccha rides of fermented and nonfermented G. biloba for the maintenance of the Th1/Th2 balance in response to extracellular pathogens.…”
Section: Figure 7 Expression Of Defensins In Cecum Tissue Measured Bymentioning
confidence: 99%